MODEL HIDRODINAMIKA 1D-2D TERINTEGRASI UNTUK ANALISIS GENANGAN PADA SISTEM DRAINASE WONOREJO-RUNGKUT KOTA SURABAYA - Irfan Adiputra Setiawan; Yang Ratri Savitri; Satria Damarnegara (Universitas Muhammadiyah Surabaya, 2026)
Urban flooding is one of the main problems in the city of Surabaya due to the increase in built-up areas and land use changes that affect the urban drainage system. Based on previous research using Analytical Hierarchy Process (AHP) method, Wonorejo primary channel and Rungkut primary channel have the highest flood management priority scale in Surabaya city with values of 0.55 and 0.53, respectively. These conditions indicate the urgency of developing a model of the distribution of puddles in the drainage system Wonorejo-Rungkut. This study aims to analyze the characteristics and distribution of inundation using an integrated 1D – 2D hydrodynamic model in the drainage system Wonorejo – Rungkut with rain re-period of 10 years. Hydrological analysis was conducted using annual maximum rainfall data for the period 2010-2024. Furthermore, rainfall plan of study area is determined through frequency distribution analysis and thiessen polygon method. Modeling is done by integrating one-dimensional flow (1D) in the drainage channel and two-dimensional flow (2D) on the land surface using PCSWMM software. Before the calibration process, mesh sensitivity and model parameters are analyzed to obtain optimal and computationally efficient simulation configuration. The results showed that the mesh size of 15 × 15 m with sampling factor 3 was chosen as the optimal configuration. Manning Overland parameters have the greatest influence on the flow velocity and depth of the puddle, while the curve number (CN) has the most influence on the area and volume of the puddle. The calibration results of the model showed a Root Mean Square Error (RMSE) of 2.43 cm and Nash–Sutcliffe Efficiency (NSE) of 89.16%, so that the model is able to represent the puddle conditions well. The simulation results showed that inundation with a depth of more than 30 cm concentrated on the eastern side of the study area dominated by ponds, while residential areas dominated by inundation with a depth of less than 20 cm. Inundation in the settlement area is affected by the influence of backwater due to high water levels in the primary channel that causes the retention of flow in the secondary and tertiary channels